2016
DOI: 10.1002/jmri.25382
|View full text |Cite
|
Sign up to set email alerts
|

Quantification of liver fat in the presence of iron overload

Abstract: Purpose To evaluate the accuracy of R2* models (1/T2* = R2*) for chemical shift-encoded magnetic resonance imaging (CSE-MRI)-based proton density fat-fraction (PDFF) quantification in patients with fatty liver and iron overload, using MR spectroscopy (MRS) as the reference standard. Materials and Methods Two Monte Carlo simulations were implemented to compare the root-mean-squared-error (RMSE) performance of single-R2* and dual-R2* correction in a theoretical liver environment with high iron. Fatty liver was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
65
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 47 publications
(69 citation statements)
references
References 52 publications
3
65
1
Order By: Relevance
“…Likewise, the presence of iron increases R2*, which causes rapid signal decay and compromises fat quantification. Although signal modeling techniques that consider the multispectral nature of fat and water have been proposed to simultaneously quantify R2* and FF, proper extraction of quantitative results in situations of high iron content might be hampered because of the rapid signal decay . In this study we evaluated the performance of an ARMA model for R2* and FF quantification, and compared the results with those obtained using a monoexponential model and an NLSQ model available in the ISMRM Fat–Water Toolbox …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Likewise, the presence of iron increases R2*, which causes rapid signal decay and compromises fat quantification. Although signal modeling techniques that consider the multispectral nature of fat and water have been proposed to simultaneously quantify R2* and FF, proper extraction of quantitative results in situations of high iron content might be hampered because of the rapid signal decay . In this study we evaluated the performance of an ARMA model for R2* and FF quantification, and compared the results with those obtained using a monoexponential model and an NLSQ model available in the ISMRM Fat–Water Toolbox …”
Section: Discussionmentioning
confidence: 99%
“…Using pure iron doped phantoms as a reference might not be the best choice, as R2* values might change slightly with fat content . Nevertheless, these changes are considered quite small compared with the effect of iron particles on R2* and, hence, it was recently proposed to treat R2* values of both species as a combined value and therefore to apply a single R2* fitting approach for simultaneous fat–water modeling …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Because of the strong paramagnetic nature of iron, f B is highly dependent on the presence of iron in the local area. A common normalR2* for all chemical species was assumed in this work, because it has been shown that, even for cases of iron overload and high hepatic fat concentrations, accurate measurements can be obtained …”
Section: Methodsmentioning
confidence: 99%
“…Additionally, a tROI was placed on representative locations on the FF map correlating to tissue samples obtained for ORO staining. Although magnetic susceptibility from hemorrhage is common in ccRCC, these Dixon methods are accurate for determination of FF even in the presence of iron overload (56). Visceral and subcutaneous fat with > 90% FF and the native kidneys with negligible FF (< 3%) served as the internal reference for adequate fitting.…”
Section: Methodsmentioning
confidence: 99%